Leonid Vladimirovich Kapilevich - Article Editorial (Бюллетень сибирской медицины, 2009)
The biography of L.V. Kapilevich, doctor of medicine, professor of the faculty chair of biophysics of medical biological faculty of Siberian State Medical University is presented. Main fields of her research activity are concerned.